2022
DOI: 10.1155/2022/6505556
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of β-Carotene Adsorption onto Acid-Activated Clays Modified by Zero Valent Iron

Abstract: The adsorption of β-carotene from crude palm oil onto acid-activated clay and clay modified by zero valent iron (ZVI) was investigated in this work. Spectroscopic studies including FTIR, XRD, and SEM were used for its characterization. The adsorption characteristics such as kinetics, mechanism, isotherms, and thermodynamics of β-carotene were studied. The kinetic data were analyzed using the pseudo-first-order kinetic equation, pseudo-second-order kinetic equation, and intraparticle diffusion model. The pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
4
0
2
Order By: Relevance
“…The analysis of the adsorbents showed that these materials are heterogeneous. We can however admit a homogeneous distribution of the adsorption sites, as justification for the conformity of the experimental results with the Langmuir model, similar observation was done by [37].…”
Section: Modeling Of Adsorption Isothermssupporting
confidence: 58%
See 1 more Smart Citation
“…The analysis of the adsorbents showed that these materials are heterogeneous. We can however admit a homogeneous distribution of the adsorption sites, as justification for the conformity of the experimental results with the Langmuir model, similar observation was done by [37].…”
Section: Modeling Of Adsorption Isothermssupporting
confidence: 58%
“…Among the different models developed to describe the kinetics of adsorption in solution, three are used in most work. These are the pseudo first order models, the pseudo second order model, and the intraparticle diffusion model [37]- [42]. These three models were therefore used here to model the kinetics of carotene adsorption by raw or modified kaolinites.…”
Section: Modeling Of Carotene Adsorption Kineticsmentioning
confidence: 99%
“…The kinetics and equilibrium modeling and calculations are done using models and techniques commonly described such as Langmuir, Freundlich, and Redlich-Paterson for isotherms models and pseudo-first-order, pseudo-second-order and Weber Morris or intra-particle diffusion for kinetic models [15,[24][25][26][27][28][29].…”
Section: Kinetics and Equilibrium Theorymentioning
confidence: 99%
“…In order to elucidate the mechanism of adsorption of NR4 onto SSC, the experimental data have been compared to the theoretical models of pseudo-first order, pseudo-second order, and intraparticle diffusion which are commonly used in the adsorption of dyes [27][28][29][30][31]…”
Section: Kinetics and Thermodynamicsmentioning
confidence: 99%